Democracy in the Indonesian Perspective: Government System - Putri, Lusiana Rahmadani; Joshua, Wang; Maharjan, Kailie (International Journal of Educational Narratives, 2023)
Background. This article is made so what we know that the western democracy that was born by the french Revolution did not bring true people’s independence,but gave rise to the power of capitalism,therefore political democracy alone is not enough to achieve true democracy ,namely people’s  soveregeighnty Purpose. There must also be economic sovereignty,which uses the basis ,that all income which recognizes the livelihood of the people must also be under the responsibility of the people. Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. Why is democracy always a theme and a moral choice in political  struggles?because humans realize that they have a moral weakness in the form of a tendency to rule and dominate others. Conclusion. If this tendency is attached to someone who happens to be holding power and there is no control mechanism that can warn and control it,then it is usually the people who will become.